Engineering Haloferax mediterranei as an Efficient Platform for High Level Production of Lycopene - Zuo, Zhen-Qiang; Xue, Qiong; Zhou, Jian; Zhao, Da-He; Han, Jing; Xiang, Hua (Frontiers in Microbiology, 2018)
Lycopene attracts increasing interests in the pharmaceutical, food, and cosmetic industries due to its anti-oxidative and anti-cancer properties. Compared with other lycopene production methods, such as chemical synthesis or direct extraction from plants, the biosynthesis approach using microbes is more economical and sustainable. In this work, we engineered Haloferax mediterranei, a halophilic archaeon, as a new lycopene producer. H. mediterranei has the de novo synthetic pathway for lycopene but cannot accumulate this compound. To address this issue, we reinforced the lycopene synthesis pathway, blocked its flux to other carotenoids and disrupted its competitive pathways. The reaction from geranylgeranyl-PP to phytoene catalyzed by phytoene synthase (CrtB) was identified as the rate-limiting step in H. mediterranei. Insertion of a strong promoter PphaR immediately upstream of the crtB gene, or overexpression of the heterologous CrtB and phytoene desaturase (CrtI) led to a higher yield of lycopene. In addition, blocking bacterioruberin biosynthesis increased the purity and yield of lycopene. Knock-out of the key genes, responsible for poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) biosynthesis, diverted more carbon flux into lycopene synthesis, and thus further enhanced lycopene production. The metabolic engineered H. mediterranei strain produced lycopene at 119.25 ± 0.55 mg per gram of dry cell weight in shake flask fermentation. The obtained yield was superior compared to the lycopene production observed in most of the engineered Escherichia coli or yeast even when they were cultivated in pilot scale bioreactors. Collectively, this work offers insights into the mechanism involved in carotenoid biosynthesis in haloarchaea and demonstrates the potential of using haloarchaea for the production of lycopene or other carotenoids.